Spin-offs and Start-ups in The Netherlands - Sierdjan Koster (European Regional Science Association (ERSA), 2003)
After a decade of widespread attention for the entrepreneurial efforts of individuals, the focus seems to partly shift to companies and their contribution to new firm formation. Especially the works of Klepper (2001) have provided a solid ground for research on the entrepreneurial activities of companies. He claims that these efforts are particularly of interest in the explanation of the evolution of economic clusters, such as the Detroit automobile industry and Silicon Valley. The evidence, brought forward by Klepper, is based on case studies and a thorough analysis of very inaccessible and complicated sources. For a structural and comparative analysis of regions and their spin-off activities an easy applicable and accessible measure is needed. In the Netherlands, the Chamber of Commerce has developed an indicator, which distinguishes between individual start-ups and ?other founding?. The latter group is designed to cover spin-off activities. Figures are published from 1995 onwards. Much in line with common studies of regional variance in entrepreneurial activity, this paper presents an explanatory model for the spatial differences in occurrence of spin-offs, based on the data from the CoC's business register. A model is defined on the one hand to explain regional differences in spin-offs, which provides a basis for structural research on cluster formation and the role of spin-offs in this process. On the other hand, it shows the differences between individual based start-ups and company driven endeavours. It is argued that these two groups of new firms are essentially distinct, and therefore cannot be explained by one and the same model. Reference: Klepper, S.J. (2001). The evolution of the U.S. automobile industry and Detroit as its capital. Carnegy Mellon University, Pittsburg Keywords: Spin-offs, spatial variances
Keywords: 330